Nicaragua : A Review of Accounting and Auditing Practices - World Bank (World Bank, 2012)
This ROSC analyzes accounting, financial reporting and auditing practices within the corporate sector in Nicaragua, using International Financial Reporting Standards (IFRS) and International Standards on Auditing (ISA) as benchmarks, and drawing on international experience and good practice in those fields. Nicaragua remains among the poorest countries of the Western Hemisphere, with 46 percent of its five million people living below the poverty line. The 2008 Gross Domestic Product (GDP) of US$6.4 billion translates into a per-capita GDP of approximately US$1,000. After average GDP growth of about 3.6 percent during 2005-08, the global financial and economic crisis lead to a contraction in real GDP of 1.5 percent in 2009. Going forward, if the private sector is to serve as an engine of growth for the Nicaraguan economy, the country needs to follow high-level accounting and auditing practices and the highest standards of corporate governance. This ROSC supports three main development objectives: (a) improving Nicaragua's investment climate; (b) ensuring the stability and fostering the development of the local financial sector and (c) advancing governance and financial accountability in both the private and public sectors. The report seeks to help the authorities address these issues by: (i) improving the technical skills of accounting and audit practitioners, (ii) strengthening the regulatory framework governing accounting and audit practices in Nicaragua, and (iii) developing the institutional capacity of the country's accounting professional bodies.